Assessment of seismic strengthening solutions for existing low-rise RC buildings in Nepal - Chaulagain, Hemchandra (2015)
The main objective of this study is to analytically investigate the effectiveness of different strengthening solutions in upgrading the seismic performance of existing reinforced concrete (RC) buildings in Nepal. For this, four building models with different structural configurations and detailing were considered. Three possible rehabilitation solutions were studied, namely: (a) RC shear wall, (b) steel bracing, and (c) RC jacketing for all of the studied buildings. A numerical analysis was conducted with adaptive pushover and dynamic time history analysis. Seismic performance enhancement of the studied buildings was evaluated in terms of demand capacity ratio of the RC elements, capacity curve, inter-storey drift, energy dissipation capacity and moment curvature demand of the structures. Finally, the seismic safety assessment was performed based on standard drift limits, showing that retrofitting solutions significantly improved the seismic performance of existing buildings in Nepal.